Evaluation and comparison of four types of bio-ceramic materials AGM MTA, Ortho MTA, pro root MTA and Cem cement in oral and dental health - Fatemeh Asadi Yalin; Maryam Tabibi; Alireza Majidi; Faezeh Kabiri; Alireza Rasouli; Mohammad Aghaali (BMC, 2024)
Abstract Background and objectives Mineral Trioxide Aggregate (MTA) is one of the main retrograde filling materials that is used today as a root end filling material and perforation repair material. This study was conducted with the aim of investigating the antibacterial and antifungal properties of four types of bio-ceramic materials, AGM MTA, Ortho MTA, Pro root MTA and Cem cement for oral and dental health. Methods In this study, the antibacterial activity of four types of bio-ceramic materials against two bacterial strains of Enterococcus faecalis (ATTC 29212), Escherichia coli (ATTC 35318) and antifungal activity against Candida albicans (ATTC 10231) were investigated using the well diffusion method. Results In the context of the relationship between the type of microorganism and the diameter of the growth inhibitory zone for each type of bio-ceramic material, there was no significant difference for Enterococcus faecalis, and a significant difference was observed for Escherichia coli and Candida albicans (p < 0.05). Conclusion The results show that each of the bio-ceramic materials AGM, Pro root, Cem cement and Ortho have antibacterial and antifungal properties. AGM MTA bio-ceramic material on Candida albicans fungus and Ortho MTA bio-ceramic material had the most effect on Escherichia coli bacteria. Therefore, the mentioned bio-ceramic materials can play a significant role in oral and dental health by providing a suitable material for restoration.